MEREFLEKSIKAN SEJARAH BURUH PETIK PERKEBUNAN TEH MELALUI KOREOGRAFI â€œSANG PEMETIKâ€ - Sherly Novalinda (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2013)
Pickers in a tea plantation present an interesting phenomenon, not only from a historical perspective but also from the point ofview of their anatomical experiences. Their hand movements are very fast, as though they are dancing on top of the tea leaves,and these movements are supported by formations that they unconsciously make in the wide expanse of the tea plantation.Based on a close observation of the tea pickers in Kayu Aro, Kerinci, Jambi, a new choreography entitled â€œSang Pemetikâ€ (ThePicker) was created, with the aim of reflecting on the history and daily experiences of the tea pickers. Using a ParticipatoryAction Research method, or PAR, the dance â€œSang Pemetikâ€ aims to make a statement that tea picking is a noble job and caneven provide inspiration for an attractive work of art.Keywords: Reflection, Tea Pickers, Choreography â€œSang Pemetikâ€